Step 1: Distribute the 2 to numbers and variables inside parentheses
(2 × x) + (2 × 3) = 4 (x - 1)
2x + 6 = 4 (x - 1)
Step 2: Distribute the 4 to numbers and variables inside parentheses
2x + 6 = (4 × x) + ( 4 × - 1)
2x + 6 = 4x+ (-4)
2x + 6 = 4x- 4
Step 3: Combine like terms (x's go with x's) by subtracting 2x to both sides
(2x - 2x) + 6 = (4x - 2x) - 4
6 = 2x - 4
Step 4: Combine like terms by adding 4 to both sides
6 + 4 = 2x - 4 + 4
10 = 2x
Step 5: Isolate x by dividing 2 to both sides
10 ÷ 2 = 2x ÷2
5 = x
x = 5
To check: plug 5 into all the x's of the equation
2(x+3)=4(x-1)
2(5+3)=4(5-1)
2(8) = 4(4)
16 = 16
Hope this helped!